(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper proposes to describe an approach used for migration of historical database from one database to required database, and setting up a daily feed from the product into the system data to have previous day reports available for current day trading. Here are different type of database we used like Ms Access, MSSQL, Oracle in source and destination. At present day there are only one language to other migration code conversion techniques. This paper attempts to give pros and cons of developed approach over existing ways in order to achieve enhanced database migration system.